Physical activity and self-esteem during pregnancy - Santos, Paula Clara (2017)
The aims of this paper are to examine the accomplishment of the recommendations of physical activity (PA) practice in accordance with the recommendations of the American College of Sports Medicine (ACSM); verify if the sociodemographic variables (SDV) influence women’s self-esteem; investigate if there are differences in pregnant women’s self-esteem who practiced or not structured physical activity (SPA) before pregnancy, and of pregnant women who met the recommendations or not during pregnancy. A sample of 44 pregnant women was evaluated in two stages: between the 10th and 13th week of pregnancy (1st trimester- 1T) and between the 20th and 23rd week of gestation (2nd trimester - 2T). The PA was assessed by accelerometry and self-esteem was assessed using the Rosenberg Self-Esteem Scale. Sociodemographic variables and SPA before pregnancy were assessed through a self-administered questionnaire. Over 60% of the sample did not meet recommendations for PA practice in any of the trimester. There were no significant differences between self-esteem for each of the SDV, with the exception of the higher monthly income (1T) and marital status (2T), associated with better self-esteem. There were significant differences in self-esteem among pregnant women or unstructured PA performed before pregnancy (1T and 2T). The completion, or not, of ACSM recommendations did not seem to impact on self-esteem during pregnancy. Most pregnant women did not met the ACSM recommendations for PA practice. It was found that marital status and higher incomes have influenced positively self-esteem, as well as the practice of SPA, before pregnancy.